L’inspectio di un anonimo investigatore pisano nella prima metà del secolo XII - Puglia, Andrea (Scrineum, 2013)
The article examines and publishes in the Appendix a document kept in the Archive of the Archbishop of Pisa, known until now only in a partial transcript, because was for a long time not available. The relevance of this document lies both in its materials and graphics characteristics , but also in its unique content, which presents a cross section of political and social life of the entourage of Bishops in the city and county in the first half of the Twelfth century. In fact, it shows the different sides of an inquest (inspectio) conducted in the diocese of Pisa by an anonymous investigator appointed by the Archbishop of Pisa Hubert in 1137. The numerous stages of the inquest were probably recorded in some files and then, with the help of judges (and law experts) and the graphic abilities of the episcopal clergy, were written in an entire parchment, with a clear and fluid book-Caroline and with a good rhetoric form. The goals of this document were surely informative, but we don’t exclude also a memorial and judicial objective. In conclusion, the inspectio give us the opportunity of studying the non-epistolographic practices of medieval communication and allows us to know a pragmatic and non-formal system of document building. This system is out of the field of notarial acts with legal effects (chartae and brevia recordationis) and different from the writing of judicial records.